Pengaruh Variasi Konsentrasi Larutan Bawang Putih (Allium sativum) Terhadap Pertumbuhan Bakteri Pada Daging Ayam - Amelya Ningsih, Putri; Advinda, Linda (Universitas Cokroaminoto Palopo, 2025)
The consumption of chicken continues to rise each year. However, the complete nutritional content in chicken meat makes it highly favored by bacteria. The allicin content in garlic can prevent the growth of various microorganisms that can cause meat spoilage. This study aims to determine the effect of varying concentrations of garlic solution (Allium sativum) on bacterial growth in chicken meat. The method used is an experiment employing a Completely Randomized Design (CRD) with three treatments: marinating chicken meat in garlic solution at concentrations of 0% (Control), 10%, and 20%, each with three replications. The research was conducted in November 2024 at the Biology Laboratory of the Faculty of Mathematics and Natural Sciences, State University of Padang. The results obtained indicate that the optimum concentration of garlic solution as an antibacterial compound is 10%, with an average total microbial count of 2,3 x 104 cfu/g